Backward Modernism and Queerly Desiring Women in Early 20th-Century British and French Fiction: Rosamond Lehmann and Jeanne Galzy (TEST Ticontre. Theory Text Translation, 2022)
This article seeks to open up comparative, transversal scholarship on the representation of queer women in Europe. Engaging critically with associations of lesbians with modernism, analysis draws on Heather Love’s concept of “backwards modernism”, and Susan Lanser’s notion of “confluence” to bring into dialogue two underexplored  novels that recount the queer experiences of young women in England and France: Rosamund Lehmann’s Dusty Answer (1927) and Jeanne Galzy’s Jeunes filles en serre chaude (1934). We identify several striking points of convergence between the novels, and argue that while they are both ambiguous in their portrayal of non-normative sexuality, they show how early queer sexual experiences are far from a “passing phase”; rather they are transformative.